Complete mitochondrial genome of freshwater shark Wallago attu (Bloch & Schneider) from Indus River Sindh, Pakistan. (2nd January 2016) - Laghari, Muhammad Younis; Lashari, Punhal; Xu, Peng; Zhao, Zixia; Jiang, Li; Narejo, Naeem Tariq; Xin, Baoping; Sun, Xiaowen; Zhang, Yan
Abstract: Complete mitochondrial genome of fresh water giant catfish, Wallago attu, was isolated by LA PCR (TakaRa LAtaq, Dalian, China); and sequenced by Sanger's method to obtain the complete mitochondrial genome. The complete mitogenome was 15, 639 bp in length and contains 13 typical vertebrate protein-coding genes, 2 rRNA and 22 tRNA genes. The whole genome base composition was estimated to be 31.17% A, 28.15% C, 15.55% G and 25.12% T. The complete mitochondrial genome of catfish, W. attu, provides the fundamental tools for genetic breeding.